PEMBERDAYAAN USAHA KREATIF DENGAN MANAJEMEN KEUANGAN UNTUK MEMAKSIMALKAN LABA DI RUMAH GEMILANG INDONESIA AL AZHAR, SAWANGAN DEPOK - Rissa Hanny; Ahmad Nurhadi Nurhadi; Nurismalatri Nurismalatri; Yhonanda Harsono; Juwita Ramadani Fitria (DEDIKASI PKM, 2020)
AbstractThis community service is entitled "Empowerment of Creative Businesses with Financial Management to Maximize Profits at Rumah Gemilang Indonesia Al Azhar, Sawangan Depok". The purpose of this service is to give guidance to students (participants) that they must become young people who have creativity in entrepreneurship, and empower creative businesses that are always innovating, in addition to providing knowledge to participants (students) about financial management methods that can provide maximum profit in entrepreneurship so that they can become successful entrepreneurs in the future. The method of implementing this service is carried out in a number of activities, namely the survey phase by visiting Gemilang Indonesia's House and then socializing there with the leadership of Gemilang's house after that compiling various things to be conveyed during the service activities to be carried out which include: preparation of material to be given, preparation of schedules provision of material, division of tasks of the devotion team and surveys to the service location. The socialization phase is before the community service activities are carried out first, the socialization phase is to make a friendship with the leaders of Rumah Gemilang Indonesia, conveying the aims and objectives of this service. At this stage also carried out the fabric of cooperation and determine the schedule of service activities. The implementing team of community service activities is 9 lecturers at the Faculty of Economics majoring in management. The dedication team provided material on Creative Business Empowerment with Financial Management to Maximize Profit at Gemilang Indonesia Al Alzhar House, Sawangan Depok, conducted by lecturers from the Faculty of Economics, Management Study Program at the University of Pamulang. The conclusion of this dedication is that participants initially did not understand how to be able to create creative businesses and implement financial management so that their businesses could obtain maximum profits. Our hope with this dedication can open insight from female and female students who will face the world of society. The material we provide is learning and practice in the field of management, especially good financial management as well as study material and input for these students to be able to implement it in daily life, so that it can help and improve scientific levels and be inspired in making home-based businesses that are will be very useful in their lives in the future.Keywords: Creative Business, Financial Management, Profit.